Wideband and compact erbium-doped fiber amplifier using parallel double-pass configuration - Hamida, B.A.; Cheng, X.S.; Harun, Sulaiman Wadi; Naji, A.W.; Arof, Hamzah; Khan, S.; Alkhateeb, W.; Ahmad, Harith (Kvantovaya Elektronika and Turpion Ltd, 2012)
In this article, a wide-band erbium doped fiber amplifier (EDFA) that operates in both C- and L-band wavelength regions is demonstrated. The amplifier employs two pieces of 1.5 m and 9 m-long erbium doped fibers (EDFs) optimized for C-band and L-band operations, respectively, in double-pass parallel configuration to achieve a wideband operation from 1530 to 1605 nm. The chirp fiber Bragg grating is used in both stages to allow a double propagation of signal and thus increases the attainable gain in both C- and L-band regions. At an input signal power of −30 dBm, a measured gain varies from 23 to 36 dB within a wide wavelength region from 1530 to 1605 nm. The corresponding noise figure varies from 5.6 to 8.2 dB within this wavelength region. The gain and noise figure of the proposed parallel configuration is much better when compared to that of a serial amplifier.